2009
DOI: 10.1042/bst0370392
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial respiratory nitric oxide reductase

Abstract: The two-subunit cytochrome bc complex (NorBC) isolated from membranes of the model denitrifying soil bacterium Paracoccus denitrificans is the best-characterized example of the bacterial respiratory nitric oxide reductases. These are members of the super-family of haem-copper oxidases and are characterized by the elemental composition of their active site, which contains non-haem iron rather than copper, at which the reductive coupling of two molecules of nitric oxide to form nitrous oxide is catalysed. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 56 publications
1
68
0
Order By: Relevance
“…Although two conserved glutamates (E198 and E267) are known to be crucial for NOR activity (24,25), their roles are not well defined (18,19). In a previous study (14), we demonstrated that one Glu, E68, is important for both iron binding and NOR activity of Fe B Mb.…”
Section: Discussion Using Rationally Designed Proteins To Address Impmentioning
confidence: 99%
See 4 more Smart Citations
“…Although two conserved glutamates (E198 and E267) are known to be crucial for NOR activity (24,25), their roles are not well defined (18,19). In a previous study (14), we demonstrated that one Glu, E68, is important for both iron binding and NOR activity of Fe B Mb.…”
Section: Discussion Using Rationally Designed Proteins To Address Impmentioning
confidence: 99%
“…3A). Since deoxy myoglobin contains Fe(II) heme that exhibits no EPR signals in X-band EPR (14), we added blue copper Cu(II)-azurin (49), a redox partner of native NOR (19), to oxidize both the reduced heme and nonheme irons in Fe (II)-I107E Fe B Mb to EPR-active Fe(III). Upon addition of Cu (II)-azurin, the oxidation of deoxy I107E Fe B Mb resulted in EPR signals at g ¼ 6.12 and 5.56, typical of a high-spin hemeFe(III).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations